FAKTOR-FAKTOR YANG MELATARBELAKANGI INTENSITAS TERAPI PERILAKU AUTISME METODE ABA (APPLIED BEHAVIOR ANALYSIS) PADA ANAK AUTIS DI RUMAH - Aisyah, Aisyah; Asmika, Asmika; Setijowati, Nanik (Fakultas Kedokteran Universitas Brawijaya, 2003)
ABSTRACT The Autism children in Indonesia had increased drastically every year. From HOPAâ€™s (Himpunan Orang tua Peduli Autisme) data, inMalang and surrounding area, there were 12 autism children in 2001, 98 children ini 2002 and increased to 120 children in June 2003.Major behavioral therapy centers in Indonesian are using ABA method for autismâ€™s therapy. The3 intensity of ABA methode needs toapply at leas 40 hours a week to get on optimal result. However, inÂ â€œ A- PLUS â€ Dharma Wanita Autistic Behavioral Therapy Center,the intensity of ABA methode didnâ€™t achieve the target. Thus the lack of time should be substitute by applying at home. The objectiveof the study is to observe the factors that influence the intensity of autistic behavioral therapy with ABA methode to the autismchildrena their home. This research is descriptive observational with cross sectional study using questionaire as instrument. The Study hasbeenÂ doneÂ 17Â parentsÂ withÂ autismÂ childrenÂ whomÂ receivedÂ behavioralÂ therapyÂ inÂ â€œA-PLUSÂ â€œDharmaÂ WanitaÂ AutisticÂ BehavioralTherapy Center Kota Malang. It was held from June until August 2003 using quota sapling technique. The result of the intensity ofABA methode on autistic children at home is sufficient (47%).The respondentâ€™s knowledge about autism and the treatment are good(59%). The fatherâ€™s occupations are merchant (70%) while the motherâ€™s are housewives (58%). The incomes of the parets are morethan 2 million rupiah monthly (59%).